You need to open the brackets to the right side such that:

`48 = x^2 + 6x`

You should move all terms to the left side such that:

`48 - x^2 - 6x = 0`

Multiplying by -1 and arranging the terms with respect to power of variable x yields:

`x^2 + 6x - 48 = 0`

Using quadratic formula yields:

`x_(1,2) = (-b+-sqrt(b^2-4ac))/(2a)`

You need to identify the coefficients a,b,c such that:

`a=1 , b = 6 , c = -48`

`x_(1,2) = (-6+-sqrt(36+192))/2 => x_(1,2) = (-6+-sqrt228)/2`

`x_(1,2) = (-6+-2sqrt57)/2 => x_(1,2) = (-3+-sqrt57)`

**Hence, evaluating the solutions to the given quadratic equation yields `x_(1,2) = (-3+-sqrt57).` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now